TEACHING RECOUNT TEXT THROUGH SCRABBLE GAME - Siti Shopiah; Resi Anggraeni (PROJECT (Professional Journal of English Education), 2018)
This research is aimed to identify whether scrabble game can improve students’ new vocabulary in recount text at eighth grade of junior high school. This research was conducted in SMPN 39 Bandung. The research was conducted by using quantitative research design, and pre-experimental research method. The researcher used one-group pretest-posttest design. The sample of this research was the eighth grade students of SMPN 39 Bandung, which consist of 32 students. In collecting the data, the researcher used test. The results of this research show that the scrabble game is able to improve students vocabulary in recount text. It is proved by the significant value using SPSS statistics 21 version to analyze the data by normality test, homogeneity and T-test. Through the normality test, the significant showed 0,090 > 0,05 and 0,061 > 0,05 which means that the data was normal. The data also homogeny with 0,348 > 0,05 as the significant value. Moreover, the T-test also showed that the significant value was 0,000 < 0,05 which means that the null hypothesis (H0) was rejected. In conclusion, applying scrabble game in teaching recount text is recommended because there is significant effect of scrabble game to students in teaching recount text.